Immune Checkpoint Inhibitors in AML-A New Frontier - Thummalapalli, Rohit; Knaus, Hanna A.; Gojo, Ivana; Zeidner, Joshua F. (Current Cancer Drug Targets, 2020)
Despite recent therapeutic advancements, acute myeloid leukemia (AML) remains a challenging clinical entity with overall poor outcomes. Given the evident role of T cell-mediated immunity in response to allogeneic stem cell transplantation and donor lymphocyte infusions, strategies that enhance immune activation and mitigate immune dysfunction represent attractive therapeutic platforms to improve clinical outcomes in AML. Pre-clinical data suggest that immune dysfunction is a major contributor to AML progression and relapse. Increased expression of immune checkpoints such as programmed death 1 (PD-1) contributes to AML immune evasion and is associated with disease progression. Immune checkpoint inhibition is being explored in AML with early evidence of clinical activity, particularly in combination with cytotoxic chemotherapy and hypomethylating agents. In this review, we explore the scientific rationale behind the use of immune checkpoint inhibition either as single agents or in combination with hypomethylating agents or cytotoxic chemotherapy and provide a clinical update of both completed and ongoing trials in AML.
Keywords: immune checkpoint inhibition